2021
DOI: 10.3390/ijerph18041758
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Nanoparticles in Male Infertility: Evidence for Induced Abnormalities in Sperm Production

Abstract: Advancement in the field of nanotechnology has prompted the need to elucidate the deleterious effects of nanoparticles (NPs) on reproductive health. Many studies have reported on the health safety issues related to NPs by investigating their exposure routes, deposition and toxic effects on different primary and secondary organs but few studies have focused on NPs’ deposition in reproductive organs. Noteworthy, even fewer studies have dealt with the toxic effects of NPs on reproductive indices and sperm paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 137 publications
(121 reference statements)
1
22
0
4
Order By: Relevance
“…An increasing number of studies is focusing on the male reproductive toxicity of SNPs [ 6 , 13 , 15 , 29 , 30 ]. SNPs can penetrate the mouse blood–testis barrier and exert their toxic actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies is focusing on the male reproductive toxicity of SNPs [ 6 , 13 , 15 , 29 , 30 ]. SNPs can penetrate the mouse blood–testis barrier and exert their toxic actions.…”
Section: Discussionmentioning
confidence: 99%
“…In males, testes are vulnerable and sensitive to exposure to numerous nanoparticles, such as carbon black nanoparticles (CBNPs) and SNPs [ 6 , 7 , 8 , 9 , 10 ]. SNPs have been observed to pass through the blood–testis barrier and distribute inside testicular tissue [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings of this study confirmed previous studies' findings, which showed that exposure to NPs caused toxic effects and the generation of infection in testes tissue. These, in part, are due to the accumulation of these particles and by the conversion of CuNPs by hydrogen into cupric ions, which are very toxic to tissues [ 30 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the cellular level, NPs affect the quality and quantity of sperm and Leydig cells. At the organ level, NPs make histological alterations, change the structure of the reproductive organ, cause damage to testes, decrease epididymis and testes weight, empty seminiferous tubules, and alter seminiferous tubules diameter and morphology ( Iftikhar et al, 2021 ). Besides male and female reproductive system and transplacental barrier, they are also involved in altering fetal growth and organ formation by causing teratogenic effects (reducing bone, sternum, toes, and fingers formation) and mortality.…”
Section: Advancements In Predicting the Nanotoxic Effects On Biological Barriersmentioning
confidence: 99%